Analysis of the Effect of Trust and Information Sharing on Supply Chain Performance with Innovation as a Mediating Variable (Study on gula semut SMEs in Kulon Progo Regency) - Ardhia Rezkitiani Andiana; Titik Kusmantini; Nilmawati Nilmawati (AIBPM Publisher, 2024)
This study aims to determine the effect of trust (X1), information sharing (X2) on supply chain performance (Y) mediated by Innovation SMEs. The population in this study were SMEs in Kulon Progo Yogyakarta. From the population taken 35 samples with non-probability sampling method. The model in this study uses Partial Least Square. And the results showed that trust and information sharing have a significant positive effect on supply chain performance mediated by SME Innovation. Applicative suggestions that can be applied are the need for trust between supply chain members. because there is still distrust between supply chain members which in the future can hinder supply chain performance. In addition, there is a need for innovations that can accelerate the performance of the supply chain such as the need for a sap drying oven, plastic caps so that the sap is not mixed with water and dirt and jerry cans are placed between 4 - 5 coconut trees which makes it easier to transport raw material supplies. With trust and information sharing can create these innovations that can affect supply chain performance.